Resource allocation and purchasing in the health sector: the English experience - Peter C Smith (The World Health Organization, 2008)
The United Kingdom of Great Britain and Northern Ireland has extensive experience in allocating health service funds to regions and localities using funding formulae. This paper focuses on England. Special attention is given to recent policy concerns to reduce avoidable health inequalities by broadening the remit of the resource allocation formulae. The paper also examines the issues that arise when seeking to allocate funds to very small organizational units, such as general practices. The English example is relevant to less-developed health systems, especially for those governments seeking to decentralize, to improve accountability and to promote equity.